Ensuring the Sustainable Development of an Industrial Enterprise on the Principle of Compliance-Safety - Pererva, P. G.; Kobielieva, T. O.; Kuchinskyi, V. A.; Garmash, Sergii; Danko, Taras (Universidad de Almería, 2021)
This article examines and explains the necessity and importance of studying the conceptual provisions of sustainable development of enterprises and organizations in the real sector of the economy, taking into account the current environmental, economic, social situation. Also, the work is developing scientific and theoretical provisions on increasing the level of safety of industrial enterprises. Special attention is paid to studying the theoretical and methodological foundations of the concept of “compliance-safety” and the development of methodological foundations of its potential use in the current conditions of the Ukrainian economy to increase the level of sustainable development of enterprises in the real sector of the economy. After analyzing the current state, methodological and practical recommendations, which are associated with potential changes in the number of compliance-safety violations in the domestic economy, were formed. In this regard, the scientific community was invited to expand the terminology base by introducing the terms “compliance safety”, which should be formulated based on the current understanding of the term “compliance”, as well as close to the concept of “economic security” and “sustainable development”. This approach makes it possible to significantly impact the sustainability of the development of industrial enterprises and the economy of the state as a whole. Thanks to this definition, it is possible to consider the dynamics of the compliance safety indicator in determining the sustainable development of an enterprise and determine the size and importance of the impact of micro and macro factors on safety. In this work, special theoretical and methodological provisions and methodological recommendations were developed for assessing the value of a comprehensive compliance safety indicator. The authors’ proposals were tested at many machine-building enterprises of the North-Eastern industrial region of Ukraine.
Keywords: compliance-safety; industrial enterprise; sustainable development